ANALISIS INDEKS KEPUASAAN MASYARAKAT TERHADAP KEBERADAAN PASAR TRADISIONAL DI KABUPATEN PEKALONGAN - Dwi Susilo; Choliq Sabana (LPPM Universitas Pekalongan, 2013)
Research with the title : Satisfaction Index Analysis Society Against Traditional Market Presence In the District Pekalongan has a purpose to know the value of Community Satisfaction Index of the existence of Traditional Markets in District Pekalongan. This study was conducted based on the population of traditional markets in the region Pekalongan 9 units, respondents were randomly selected based on the number of merchants who sell and market visitors in every market studied using stratified random sampling technique of sampling by looking at the proportion of each place. The respondents include: a. Traders are user kiosks, los, and lapak.dan b. Visitor market. Indicators of market service user community satisfaction is measured by the decree PAN Number: Kep/25/M.PAN/2/2004 general guidance on public satisfaction indexing services unit of government agencies. The results showed that the results of the calculation of the index of satisfaction with the services of traditional markets in the District 9 Pekalongan show that the perception of the average trader satisfaction with services market by 70.84% or the quality of service B (good). And the results of the calculation of the index of satisfaction with the services of traditional markets in the District 9 Pekalongan show that the perception of the average appraisal of satisfaction with the service market of 67.83 in the quality of service B (good)The Keywords: Traditional Markets, Services and Community Satisfaction Index